Molecular Epidemiological Investigation of Human Parainfluenza 3 Virus Outbreak in a Pediatric Bone Marrow Transplantation Unit. (4th October 2017) - Stapleton, Patrick; Perusini, Stephen; Thomas, Angela; Science, Michelle; Schechter-Finkelstein, Tal; Gubbay, Jonathan B; Patel, Samir; Yau, Yvonne
Abstract: Background: Human parainfluenza virus 3 (hPIV3), a common cause of respiratory infections in children, can cause nosocomial outbreaks in patients undergoing hematopoietic stem cell transplantation, resulting in significant morbidity and mortality. Between July and August 2016, an increased number of hPIV3 infections were noted in a pediatric bone marrow transplant unit (BMT). Two patients were identified in late July and 4 patients in August. We undertook molecular typing of hPIV3 to determine whether cases represented multiple introductions of community virus strains or patient to patient transmission of a single strain. Previous reports of molecular typing have targeted either the F (fusion protein) gene or HN (hemagglutinin-neuraminidase) gene. We compared results using both methods direct from clinical specimens. Methods: Nasopharyngeal (NP) swabs from 6 patients in BMT ward and 6 patients hospitalized on other wards had hPIV3 detected by the Luminex NxTAG Respiratory Pathogen Panel over 2 months. For the F gene a single pair of primers were used to first amplify then sequence a 278 basepair (bp) region by reverse-transcriptase PCR (RT-PCR). For HN gene a 1719 bp region was amplified using nested RT-PCR, then sequenced with 6 sets of overlapping primers. The resulting contigs were assembled manually with ContigExpress. Phylogenetic analysis of assembled sequences was performed in MEGA7 using the maximum likelihood method. Results: For the HN gene sequence of 1715 bp was obtained for 10 of 12 patients (5 in each group). Phylogenetic analysis of HN sequences indicated 2 distinct hPIV3 lineages (Figure 1). The 5 BMT patients differed by a maximum of 1bp, while 5 samples from other wards differed by 14 to 57 bp. For the F gene only 98 bp of common sequence was obtained for 7 patients, all of whom had HN gene sequences available. Phylogenetic analysis of F gene sequence also supported the presence of 2 distinct lineages. Conclusion: Molecular typing of hPIV3 suggests there was transmission of a single hPIV3 strain within the BMT unit despite protective isolation of all BMT patients in positive pressure single rooms and the use of contact and droplet precautions for infected cases. We found sequencing the HN gene more informative than sequencing the F gene. Disclosures: All authors: No reported disclosures.